Proceedings of the International Conference on Computing and Communication Systems I3CS 2016, NEHU, Shillong, India - Mandal, J. K.; Saha, Goutam; Kandar, Debdatta; Maji, Arnab Kumar (Lecture Notes in Networks and Systems, 2018)
The volume contains latest research work presented at International Conference on Computing and Communication Systems (I3CS 2016) held at North Eastern Hill University (NEHU), Shillong, India. The book presents original research results, new ideas and practical development experiences which concentrate on both theory and practices. It includes papers from all areas of information technology, computer science, electronics and communication engineering written by researchers, scientists, engineers and scholar students and experts from India and abroad.